Philosophical concepts of man in the context of medical sciences - Żołnierz, Joanna (Journal of Education, Health and Sport, 2018)
Introduction: The search for answers to questions about human reality combines philosophy with science. The analysis of trends shaping medical science shows how strongly they are embedded in certain philosophical movements. And although referring to the philosophical assumptions of theories adopted in medicine and health sciences, especially for practitioners, may seem like an unnecessary effort, it is justified and sensible. An in-depth understanding of the impact, that philosophical concepts of man have had on the shaping of medicine and the organization of health care, gives us the opportunity to improve our actions. Objective: The article will present the biomedical and holistic paradigms of medical sciences. Another aim is to identify movements and philosophical conception of man, which contributed to the formation of these paradigms. Conclusions: The article presents two philosophical concepts of man: monistic and dualistic. Each of these concepts has a big influence on the shaping of paradigms functioning within the medical sciences. Understanding these relationship is especially important for those, who are involved in medical or nursing practice. The philosophical concepts of man shape not only our way of understanding medicine or nursing as scientific disciplines. Understanding the theoretical foundations of concepts of man is especially important in making a moral assessment of our actions.